Being humorous and seeking diversion: Promoting healthy coping skills among LGBTQ+ youth. Issue 1 (2nd January 2018) - Craig, Shelley L.; Austin, Ashley; Huang, Yu-Te
ABSTRACT: LGBTQ+ youth encounter pervasive stigma-related stress that requires effective coping skills. This study explored the coping patterns of LGBTQ+ youth participants ( N = 30) in a cognitive-behavioral therapy-based coping skills training. Participants, 15–18 years old with a range of gender, sexual, racial and ethnic identities, completed a coping skills inventory (A-COPE) with 12 subscales at two time points. Based on the stigma-coping framework, coping skills were broadly classified as disengagement or engagement strategies. LGBTQ+ youth were most likely to utilize avoiding problems as a strategy to cope with stress, followed closely by being humorous, relaxing, and ventilating feelings. Notably, seeking professional and spiritual support were the least adopted coping strategies. Post-intervention, participants reported significant increases in the areas of primary control (solving family problems) and secondary control (seeking spiritual support, seeking diversion, engaging in demanding activities, and being humorous). The findings demonstrate the versatility of LGBTQ+ youth's coping strategies and show the potential of the AFFIRM intervention to promote engagement coping patterns among this population.